Utilizing exosomes as sparking clinical biomarkers and therapeutic response in acute myeloid leukemia - Wandi Wang; Xiaofang Wu; Jiamian Zheng; Ran Yin; Yangqiu Li; Xiuli Wu; Xiuli Wu; Ling Xu; Ling Xu; Zhenyi Jin; Zhenyi Jin (Frontiers in Immunology, 2024)
Acute myeloid leukemia (AML) is a malignant clonal tumor originating from immature myeloid hematopoietic cells in the bone marrow with rapid progression and poor prognosis. Therefore, an in-depth exploration of the pathogenesis of AML can provide new ideas for the treatment of AML. In recent years, it has been found that exosomes play an important role in the pathogenesis of AML. Exosomes are membrane-bound extracellular vesicles (EVs) that transfer signaling molecules and have attracted a large amount of attention, which are key mediators of intercellular communication. Extracellular vesicles not only affect AML cells and normal hematopoietic cells but also have an impact on the bone marrow microenvironment and immune escape, thereby promoting the progression of AML and leading to refractory relapse. It is worth noting that exosomes and the various molecules they contain are expected to become the new markers for disease monitoring and prognosis of AML, and may also function as drug carriers and vaccines to enhance the treatment of leukemia. In this review, we mainly summarize to reveal the role of exosomes in AML pathogenesis, which helps us elucidate the application of exosomes in AML diagnosis and treatment.